Development of Submission Box with Data Storage - Mohamad Nadzrul Irfan M. N.; Muhammad Aidid Afian A. R; Ma'Radzi, Ahmad Alabqari (Multidisciplinary Applied Research and Innovation, 2024)
Most assignments delivered in universities cannot be monitored due to the large number of people who send them, and most of them are vulnerable to physical factors such as rain, security, and so on. The main problem was the lack of a previous method to document and track submitted tasks that were harmed by weather conditions. To overcome these challenges, a submission box with internal data storage was developed using an Arduino UNO as a microprocessor. This paper describes and discusses the development of a submission box with internal data storage utilising Tinkercad Simulation and an Arduino IDE. Additionally, this thesis presents the management of the submission box with internal data storage. Both modelling findings and experimental data are presented and discussed. This paper has examined both experimental findings related to the submission box prototype with internal data storage. The simulation and experiment data support the theoretical findings. The development of this system offers a solution to enhance productivity in university on work submission.